Assessing the Impacts of Anxiety and Gender on Student Attitudes Toward Computer Learning Technology in a Saudi Nursing Academic Environment - Samarkandi, Osama A.; Adel S. Bashatah; Almotairi, Sultan H.; Bokhari, Mahdiah A.; Mohammed Aljanoubi; Almajid, Yousef; Sonbol, Yazeed; Alsalam, Adnan A. (International Journal For Research In Health Sciences And Nursing, 2015)
Computer knowledge and skills are becoming essential components technology in nursing education. Saudi nurses must be prepared to utilize these technologies for the advancement of science and nursing practice in local and global communities. Little attention has been directed to students’ attitudes about computer usage in academic communities in Saudi Arabia. Their attitudes about the use of computers for the enhancement of learning are relatively unknown. Few research studies have been identified that explicate Saudi Arabian nursing students’ attitudes toward computer usage for the acquisition of knowledge and skills. Males and females matriculate at King Saud University (KSU), but attend classes in gender-specific groups. This descriptive correlation study will contribute to the body of knowledge related to nursing students’ attitudes toward computer usage in their baccalaureate education at KSU. The research included all students enrolled in the College of Nursing at KSU in Riyadh, in the summer semester of the academic year 2009-2010. The total number of undergraduate nursing students were 600; 195 were males and 405 were females (KSU, 2008). The findings (n = 335; nm= 133 & nf = 222) suggest that females were more anxious about computer usage (Mean=31.5; 32.7) than males. None of the independent variables explained the variance in the dependent variable, computer usage. Findings did indicate that students had less anxiety if they had access to a computer at home or at school; their anxiety was even less if they had computer exposure at both home and school. Implications of these findings are presented with regard to educating future nurses at KSU for complex roles in health care systems. The study also raises issues about the possibility of planning intervention studies for future research about computer learning, possibly using simulation-based approaches and virtual systems. Issues regarding gender, socioeconomic status, age, learner attitudes, and other variables will need to be systematically investigated. Future studies should assist with the unraveling of traditional cultural issues, including gender-specific roles and expectations for computer usage in nursing and health care delivery.